2017
DOI: 10.1038/ja.2017.64
|View full text |Cite
|
Sign up to set email alerts
|

The salicylidene acylhydrazide INP0341 attenuates Pseudomonas aeruginosa virulence in vitro and in vivo

Abstract: Pseudomonas aeruginosa is an opportunistic pathogen that can be very hard to treat because of high resistance to different antibiotics and alternative treatment regimens are greatly needed. An alternative or a complement to traditional antibiotic is to inhibit virulence of the bacteria. The salicylidene acylhydrazide, INP0341, belongs to a class of compounds that has previously been shown to inhibit virulence in a number of Gram-negative bacteria. In this study, the virulence blocking effect of INP0341 on P. a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 68 publications
0
18
0
4
Order By: Relevance
“…[222][223][224] Salicylidene acylhydrazides (SAHs) represent aw ell-known class of T3SS inhibitors that have been extensively studied in various pathogens including P. aeruginosa and Salmonella typhimurium. [225][226][227][228][229] However, these SAHs seem to function through several mechanisms which need further elucidation. [225][226][227][228][229] However, these SAHs seem to function through several mechanisms which need further elucidation.…”
Section: Type III Secretion Systems (T3ss)mentioning
confidence: 99%
See 1 more Smart Citation
“…[222][223][224] Salicylidene acylhydrazides (SAHs) represent aw ell-known class of T3SS inhibitors that have been extensively studied in various pathogens including P. aeruginosa and Salmonella typhimurium. [225][226][227][228][229] However, these SAHs seem to function through several mechanisms which need further elucidation. [225][226][227][228][229] However, these SAHs seem to function through several mechanisms which need further elucidation.…”
Section: Type III Secretion Systems (T3ss)mentioning
confidence: 99%
“…[224] Diverse SAH derivatives such as INP0341 have been synthesized and were found to attenuate bacterial pathogenesis. [225][226][227][228][229] However, these SAHs seem to function through several mechanisms which need further elucidation. [230] In ad ifferent approach, screening of compound libraries with acellular reporter assay revealed phenoxyacetamide MBX 1641 to be ap otent inhibitor of P. aeruginosa T3SS (IC 50 % 10 mm)w ith al ow toxicity against eukaryotic cells ( Figure 16).…”
Section: Type III Secretion Systems (T3ss)mentioning
confidence: 99%
“…[221] Es wurde eine Reihe von T3SS-Inhibitoren entdeckt, welche die Regulation der Expression des T3SS,d ie Synthese der nadelartigen Struktur sowie die Sekretion und Tr anslokation von Effektorproteinen beeinflussen (Abbildung 16). [225][226][227][228][229] Diese SAHs scheinen über verschiedene Mechanismen zu wirken, welche noch genauer aufgeklärt werden müssen. [224] Vielfältige SAH-Derivate,wie INP0341, wurden synthetisiert und führten zu einer Verringerung der bakteriellen Pathogenität.…”
Section: Typ-iii-sekretionssysteme (T3ss)unclassified
“…[224] Vielfältige SAH-Derivate,wie INP0341, wurden synthetisiert und führten zu einer Verringerung der bakteriellen Pathogenität. [225][226][227][228][229] Diese SAHs scheinen über verschiedene Mechanismen zu wirken, welche noch genauer aufgeklärt werden müssen. [230] In einem weiteren Ansatz konnte durch ein Screening von Substanzbibliotheken in einem zellulären Reporter-Assay das Phenoxyacetamid MBX 1641 als wirksamer Inhibitor gegen das T3SS in P. aeruginosa (IC 50 % 10 mm)i dentifiziert werden (Abbildung 16).…”
Section: Typ-iii-sekretionssysteme (T3ss)unclassified
“…Antibodies binding to proteins at the tip of the needle structure block T3SS function and promote passive protection in animal infection models 1 . In addition, mutation of the T3SS reduces infection of eukaryotic cells and mice 2,3 . The T3SS is conserved among a large number of Gram-negative pathogens and research over the last decades has demonstrated that the T3SS constitutes a validated target for the development of novel pathogen selective therapeutic agents 4 .…”
mentioning
confidence: 99%